THE EFFECT OF SOCIAL MEDIA CONTENT ON CUSTOMER ENGAGEMENT AND ITS IMPACT ON CUSTOMER INTENTION - Naomi Miryam; Ferdi Antonio (Jurnal Manajemen Pemasaran, 2022)
The rising number of fitness centers compelled business professionals to implement effective marketing techniques. This study aimed to analyze and test the antecedent of content in social media marketing, namely social interaction (SI), service provider interaction (SPI), self-concept (SC), functional information (FI), and entertaining information (EI) on customer engagement, and its effect on continuous usage intention (CUI) and positive electronic word of mouth (E-WOM), moderated by health literacy. The conceptual framework was empirically tested on customers of the fitness club. A quantitative survey employing the cross-sectional data method was done. The respondents were selected based on specific criteria, and data was collected using a Likert-scaled online questionnaire. The sample consisted of 236 respondents, and data analysis was conducted using Partial Least Square-Structural Equation Modelling (PLS-SEM). The results demonstrated that engagement has an effect on continuous usage intention (CUI) and the propensity to spread positive E-WOM (PEW). In addition, Health Literacy has not demonstrated a substantial moderating influence. In exchange, health literacy is characterized as a predictor of moderation. The research outcome may have managerial consequences for the fitness facility administration discussed in this article.